Peran Badan Permusyawaratan Desa dalam Pengelolaan Aset Desa: Kata Kunci: Aset Desa, BPD, Dana Desa, dan Pengawasan - Mahenda Erarefra Putra; Aprina Nugrahesthy Sulistya Hapsari (Jurnal Akuntansi, 2020)
This study aims to describe the role of Badan Permusyawaratan Desa (BPD) in village assets management in Purworejo village, Purworejo Klampok sub-district, Banjarnegara Regency. Village assets are interesting to study because of the phenomena that occur indicate weaknesses in village assets management. On the other hand, village assets are an inseparable part of the government's efforts to increase village values ??and advance national development. This study uses a qualitative descriptive approach with in-depth interview method and observation as data collection methods. The participants in this study are members of BPD 2018-2024 and members of the community involved in village assets management. The results of this study indicated that the role of BPD in village assets management are apparent in all stages, especially in the stages of planning, procurement, transfers, administration, reporting and supervision. However, the role of the BPD is not too optimal due to constraints related to limited human resources, especially regarding each BPD members’ educational background and their availability of time. In addition, the community itself still does not have a deep understanding of the role of BPD, so they feel that they have not been directly affected by the existence of BPD.